In vitro toxicity assessment of respirable solid surface composite sawing particles - Mandler, W Kyle; Kang, Seungkoo; Farcas, Mariana; Qi, Chaolong; Friend, Sherri A; Qian, Yong (Toxicology and industrial health, 2020)
Solid surface composites (SSCs) are a class of popular construction materials composed of aluminum trihydrate and acrylic polymers. Previous investigations have demonstrated that sawing SSC releases substantial airborne dusts, with a number-based geometric mean diameter of 1.05 µm. We reported that in mice, aspiration exposure to airborne SSC dusts induced symptoms of pulmonary inflammation at 24-h postexposure: neutrophilic influx, alveolitis, and increased lactate dehydrogenase (LDH) and pro-inflammatory cytokine levels in lavage fluid. The particles appeared to be poorly cleared, with 81% remaining at 14-day postexposure. The objective of this study was to determine the toxicity specifically of respirable particles on a model of human alveolar macrophages (THP-1). The relative toxicities of subfractions (0.07, 0.66, 1.58, 5.0, and 13.42 µm diameter) of the airborne particles were also determined. THP-1 macrophages were exposed for 24 h to respirable particles from sawing SSC (0, 12.5, 25, 50, or 100 µg/ml) or size-specific fractions (100 µg/ml). Exposure to respirable SSC particles induced THP-1 macrophage toxicity in a dose-dependent manner. Viability was decreased by 15% and 19% after exposure to 50 and 100 µg/ml SSC, respectively, which correlated with increased cell culture supernatant LDH activity by 40% and 70% when compared to control. Reactive oxygen species (ROS) production and inflammatory cytokines were increased in a dose-dependent manner. A size-dependent cytotoxic effect was observed in the cells exposed to subfractions of SSC particles. SSC particles of 0.07, 0.66, and 1.58 µm diameter killed 36%, 17%, and 22% of cells, respectively. These results indicate a potential for cytotoxicity of respirable SSC particles and a relationship between particle size and toxicity, with the smallest fractions appearing to exhibit the greatest toxicity.